Capital Structure, Precautionary Balances, and Valuation of the Firm: The Problem of Financial Risk - Tinsley, P. A. (Journal of Financial and Quantitative Analysis, 1970)
P. A. Tinsley, Capital Structure, Precautionary Balances, and Valuation of the Firm: The Problem of Financial Risk, The Journal of Financial and Quantitative Analysis, Vol. 5, No. 1 (Mar., 1970), pp. 33-62